MAIN APPROACHES TO THE FORMATION OF RECEPTIONS, METHODS AND METHODS OF TEACHING HISTORY, THEIR ORDERING AND SYSTEMATIZATION (Pedagogy of Higher and Secondary Education, 2006)
The article deals with the questions of forming of system of mode and methods in a historical education as a necessity that is naturally stipulated by the condition of reformation and closing to the European and world standards. Some aspects of practical realization of this task are revealed.